(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper presents the main findings of a survey conducted to evaluate the e-business readiness of small and medium enterprises in Jordan. A questionnaire was administered in the late 2011 to 200 SME operating in different economical sectors in the country. The survey aimed at analyzing the e-business readiness of these organizations by exploring three levels of analysis: the status of the ICT infrastructure, a general assessment of ICT competencies in businesses, an analysis of needs for training and an evaluation of the maturity of the market and the surrounded environment. The results show that the ICT, mainly used for administrative and commercial purposes, is considered as an investment. Its budget is allocated most of the time towards upgrading, creating new services and maintenance. They suggest a strong adoption of basic ICT, such as personnel computers, Internet access, and Web site. Exploitation of these technologies has been marked by the improvements in work organization, time saving and cost reduction. However, most of the SMEs faced problems in training employees, implementation costs and lack of maturity of the market. At the national level, the results show that more maturity is needed in the technical, business, and legal infrastructure.